Toll-like receptor activation and hypoxia use distinct signaling pathways to stabilize hypoxia-inducible factor 1α (HIF1A) and result in differential HIF1A-dependent gene expression. - Jantsch, J; Wiese, M; Schödel, J; Castiglione, K; Gläsner, J; Kolbe, S; Mole, D; Schleicher, U; Eckardt, K; Hensel, M; Lang, R; Bogdan, C; et al. (2011)
HIF1A is a transcription factor that plays a central role for the adaptation to tissue hypoxia and for the inflammatory response of myeloid cells, including DCs. HIF1A is stabilized by hypoxia but also by TLR ligands under normoxic conditions. The underlying signaling events leading to the accumulation of HIF1A in the presence of oxygen are still poorly understood. Here, we show that in contrast to hypoxic stabilization of HIF1A, normoxic, TLR-mediated HIF1A accumulation in DCs follows a different pathway that predominantly requires MYD88-dependent NF-κB activity. The TLR-induced HIF1A controls a subset of proinflammatory genes that are insufficiently induced following hypoxia-mediated HIF1A induction. Thus, TLR activation and hypoxia stabilize HIF1A via distinct signaling pathways, resulting in differential HIF1A-dependent gene expression.